Novel sensor developments for photon science at the MPG semiconductor laboratory - Ninkovic, J.; Bähr, A.; Richter, R. H.; Treis, J. (Frontiers in Physics, 2024)
The world of photon science experiences significant advancements since the advent of synchrotron light sources with unprecedented brilliance, intensity and pulse repetition rates, with large implications on the detectors used for instrumentation. Here, an overview about the work on this field carried out at the semiconductor laboratory of the Max-Planck-Society (MPG HLL) is given. Main challenges are high dynamic range to resolve faint features at the fringes of scatter images as well as structures in bright peaks, and high bandwidth to fully exploit the fast timing capability of the source.A newly developed device to improve the signal-to-noise-ratio (SNR) at high bandwidths is the socalled MARTHA (Monolithic Array of Reach-Through Avalanche Photodiodes) structure, which integrates an array of APDs on a monolithic substrate. The reach-through architecture assures near 100% fill factor and allows implementing a thin entrance window with optimized quantum efficiency (QE) for low energy X-rays. The structures operate in proportional mode with adjustable gain, and can serve as a drop-in replacement for PAD detectors in hybrid pixel systems.A more sophisticated solution for low to medium frame rate applications with high contrast requirement are pnCCDs with high dynamic range in the pixel area featuring DEPFET based readout nodes with non-linear amplification (NLA). The high dynamic range mode has been demonstrated for pnCCD devices with a pixel size down to 75 µm 2 . Framerates of up to 1 kHz are possible for a 1 Megapixel detector. Small size prototypes of these structures have recently been manufactured.Modified DEPFET structures with build-in NLA are also used to implement active pixel detectors optimized for high dynamic range. Successfully prototyped for the DSSC sensors (DEPFET Sensor with Signal Compression) at the XFEL, these structures are increasingly being used in applications requiring high contrast and intensity, e.g. TEM imaging. Charge handling capability and output characteristics can be tailored to the requirements, as well as pixel geometry and size. The large intrinsic gain of the DEPFET provides excellent SNR even at fast timing. Pixels can be read with a speed of 100 ns, the resulting frame rate depends on the degree of readout parallelization.